Earth as an evolving planetary system - Condie, Kent C. (Elsevier/Academic Press, 2011)
Earth as an Evolving Planetary System, Second Edition, examines the various subsystems that play a role in the evolution of the Earth. These subsystems include such components as the crust, mantle, core, atmosphere, oceans, and life. The book contains 10 chapters that discuss the structure of the Earth and plate tectonics; the origin and evolution of the crust; the processes that leave tectonic imprints in rocks and modern processes responsible for these imprints; and the structure of the mantle and the core. The book also covers the Earth's atmosphere, hydrosphere, and biosphere; crustal and mantle evolution; the supercontinent cycle; great events in Earth history; and the Earth in comparison to other planets. This book is meant for advanced undergraduate and graduate students in Earth Sciences, with a basic knowledge of geology, biology, chemistry, and physics. It also may serve as a reference tool for specialists in the geologic sciences who want to keep abreast of scientific advances in this field. Slides of all figures in the book can be downloaded on the companion site: http://www.elsevierdirect.com/companion.jsp?ISBN=9780123852274 Kent Condie's corresponding interactive CD, Plate Tectonics and How the Earth Works, can be purchased from Tasa Graphic Arts here: http://www.tasagraphicarts.com/progptearth.html Two new chapters on the Supercontinent Cycle and on Great Events in Earth history New and updated sections on Earth's thermal history, planetary volcanism, planetary crusts, the onset of plate tectonics, changing composition of the oceans and atmosphere, and paleoclimatic regimes Also new in this Second Edition: the lower mantle and the role of the post-perovskite transition, the role of water in the mantle, new tomographic data tracking plume tails into the deep mantle, Euxinia in Proterozoic oceans, The Hadean, A crustal age gap at 2.4-2.2 Ga, and continental growth.